(untitled) (Advances in Applied Mathematics and Mechanics, 2022)
We have analyzed the kinetics of solid circular particles interacting with fluid, outer boundary and internal square shaped obstacles tilted at a 45^° angle. The effects on the motion of particle due to collision with obstacles and wall are inspected. An Eulerian approach is used to study the behavior of particle in the fixed computational mesh. The interactions between fluid, particles and obstacles have been carried out in the whole domain by using fictitious boundary method (FBM). In this work, the particulate flow simulations are computed by using finite element solver FEATFLOW. Numerical results are presented by assigning different alignments to the obstacles and varying their positions in the domain. Particle-wall, particle-particle and particle-obstacle collisions are treated by applying a modified collision model proposed by Glowinski et al. The rapid change in drag forces acting on obstacles due to nearby passing particles and its effect on the fluid motion has been investigated.